2015
DOI: 10.1186/s12902-015-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of treatment with liraglutide on atherothrombotic risk in obese young women with polycystic ovary syndrome and controls

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is associated with obesity and increased cardiovascular (CV) risk markers. In this study our aim was to assess the effects of six months treatment with liraglutide 1.8 mg od on obesity, and CV risk markers, particularly platelet function, in young obese women with PCOS compared to controls of similar age and weight.MethodsCarotid intima-media wall thickness (cIMT) was measured by B-mode ultrasonography, platelet function by flow cytometry, clot structure/lysis by turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 47 publications
0
41
1
Order By: Relevance
“…The search returned 3264 articles ( Figure 1 ). Fifty-nine full text articles were retrieved for further evaluation and 17 articles [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] reporting 14 studies met the inclusion criteria. Of these 17 articles, one study was reported across two articles [ 31 , 32 ] and one study [ 35 ] reported data across different time points [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search returned 3264 articles ( Figure 1 ). Fifty-nine full text articles were retrieved for further evaluation and 17 articles [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] reporting 14 studies met the inclusion criteria. Of these 17 articles, one study was reported across two articles [ 31 , 32 ] and one study [ 35 ] reported data across different time points [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interventions varied across the included studies (diet, diet + behavior change program, diet + Metformin, diet + anti-obesity drug, anti-obesity drug, diet + anti-obesity drug + exercise, bariatric surgery, and various exercise training programs), as did the duration of interventions. Nine studies were designed with the specific aim of weight loss [ 34 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 46 ], while the remaining five studies did not state if the aim was weight loss [ 30 , 31 , 33 , 40 , 44 ]. The sample size of the studies varied from 31 to 1016.…”
Section: Resultsmentioning
confidence: 99%
“…Glucagon-like peptide 1 receptor agonists (GLP-1RA) cause weight loss in patients with T2D and obesity, and have been tested in PCOS in smaller studies. [3][4][5][6][7] None of these studies was placebo-controlled, and often metformin was allowed as a pre-or co-medication. Therefore, we performed a randomized clinical trial (RCT) investigating whether monotherapy with the GLP-1RA liraglutide could reduce liver fat content, VAT and the prevalence of NAFLD in women with PCOS.…”
mentioning
confidence: 99%
“…In another study, 6-month intervention with liraglutide was associated with significant reduction in atherothrombosis markers, including inflammation, endothelial function and clotting. The positive effect equally affected young obese women with PCOS and controls [58].…”
Section: Rasmussen Andmentioning
confidence: 93%
“…Lindenberg [55] x / Kahal et al [58] x / / Jensterle Sever et al [53] x / x / / Jensterle et al [60] x x x / x Jensterle et al [56] x x Jensterle et al [57] x x x x…”
Section: Rasmussen Andmentioning
confidence: 99%